Predicting defects and material quality in castings by means of computational determination of flow length values - Hilbinger, Rolf Michael; Lohmüller, Andreas; Köpf, Johannes; Singer, Robert (International Journal of Cast Metals Research, 2011)
A new criterion for the optimisation of casting design by numerical simulation is proposed. Based on the determination of flow length values during filling in castings, possible locations of defects can be predicted together with their effect on mechanical properties. This approach is demonstrated for a magnesium casting with special emphasis on comparison with experimental results. © 2011 W. S. Maney & Son Ltd.
Keywords: Fill pattern; Filling related defects; Flow length; Numerical simulation